Role of doubling rate of hCG in predicting early pregnancy loss: a retrospective analysis - Xiaoping Wang; Fangxiang Mu; Qiliang Jian; Fang Wang (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective This study aims to explore whether the human chorionic gonadotropin (hCG) doubling rate every 48 h (HDR) predicts early pregnancy outcomes in women with pregnancy loss.Methods The early clinical pregnancy outcomes in 257 women with a history of pregnancy loss were analyzed in this retrospective study. The optimal cutoff value of HDR was determined by the receiver operating characteristic (ROC) curve and the Youden index. The primary outcome was pregnancy loss occurring before 12 weeks of gestation.Results A total of 257 patients were enrolled in this study. According to the pregnancy outcome at 12 weeks of gestation, the patients were divided into ongoing pregnancy (N = 198) and early pregnancy loss (EPL) groups (N = 59). In the total study population, the HDRs in ongoing pregnancy group were significantly higher than those in EPL group at specific intervals of hCG levels: 150–400 mIU/ml, 400–800 mIU/ml, and 3200–6400 mIU/ml. The corresponding thresholds were 1.855, 2.219, and 1.730, respectively (p < 0.05). A similar result was observed among patients with recurrent pregnancy loss (RPL) across the intervals of 400–800 mIU/ml, 800–1600 mIU/ml, 3200–6400 mIU/ml, and 20000–30000 mIU/ml, with corresponding thresholds of 2.219, 1.812, 1.730, and 1.450, respectively.Conclusions HDR may serve as an evaluative tool for predicting the risk of EPL in women with pregnancy loss. Differences in the intervals showing predictive value between women with and without RPL imply that individualized interpretation of HDR may be warranted in these subgroups. However, given the limited sample size, especially within the EPL group, these findings should be interpreted with caution.